X Chromosome Pericentric Inversion: Report of a Case with 46,X,inv(X)(p11.2q26) and a Mini-Review of the Literature - Emine Göktaş; Betül Okur Altındaş; Ayşe Gül Zamani; Mahmut Selman Yıldırım (Gazi Medical Journal)
Pericentric inversions arise from double breaks on opposite arms of the chromosome, followed by 180° rotation and reintegration of the broken segment. Carriers of an inversion are mostly phenotypically healthy. However, they may have some clinical implications, including reproduction anomalies due to imbalanced gamete production. Here, we highlighted the phenotypical variability of X chromosome inversions by reporting a case. The female proband who had recurrent spontaneous abortions was admitted to the Medical Genetics polyclinic. After clinical evaluation, conventional Giemsa-banded karyotyping was performed. The result was 46,X,inv(X)(p11.2q26). Segregation analysis of the family members revealed that she inherited the pericentric inversion from her father and passed it on to her daughter. Detailed genetic counseling was provided to the family. The significance of X chromosome pericentric inversions in the literature was discussed with regard to their phenotypical relevance to enhance our understanding of clinical variability caused by chromosomal inversions.